1990
DOI: 10.1007/bf00270058
|View full text |Cite
|
Sign up to set email alerts
|

Protoplast production in Chondrus crispus gametophytes (gigartinales, rhodophyta)

Abstract: Protoplasts were isolated from female gametophytes of Chondrus crispus (Stackh.) using commercial cellulase and various carrageenases prepared from marine bacteria. Depending on the nature of the donor tissue (apices or whole thallus, wild or cultivated strains), yields ranged from 1.0-8.5×10(8) protoplasts per gram of fresh tissue. Preincubating the tissue with a potassium chelator, Kryptofix 222, enhanced protoplast yields by 30-50 %. Based on staining with fluorescein diacetate most protoplasts were viable.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…The efficiency of procedure using simultaneously carrageenase and cellulase on Chondrus crispus suggest that the destruction of cellulose facilitates access to carrageenan. This fact indirectly confirms the results of Le Gall et al (1990), who found that the carrageenase-cellulase couple gives optimal production of protoplasts from Chondrus crispus. An increase of incubation time does not appear to be an important factor to improve the protein extraction from Chondrus crispus (Table 4).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The efficiency of procedure using simultaneously carrageenase and cellulase on Chondrus crispus suggest that the destruction of cellulose facilitates access to carrageenan. This fact indirectly confirms the results of Le Gall et al (1990), who found that the carrageenase-cellulase couple gives optimal production of protoplasts from Chondrus crispus. An increase of incubation time does not appear to be an important factor to improve the protein extraction from Chondrus crispus (Table 4).…”
Section: Discussionsupporting
confidence: 91%
“…Epiphytes and other contaminants (sand, shells) were eliminated by successive washings with sea water and deionised water. The algal material (10 g) was cut into 0.5-1 cm pieces (Le Gall et al, 1990), suspended in the incubation medium containing appropriate enzymes and buffers (Tables 1, 2), and incubated for 2 or 14 h under the optimum activity conditions (pH, temperature) for the enzyme tested (Table 1). NaCI (500 mM), MgCI2 (40 mM), KC1 (5 mM) were added into the incubation medium as described by Le Gall et al (1991) for the production of Chondrus crispus protoplasts with carrageenase and cellulase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition volume was adapted to the new fresh weight in such a way that the nutrient load for each treatment was kept constant during the experiment. During the last 2 wk of the experiment, 47.8 μM GeO 2 was added to the medium to suppress diatom growth (Le Gall et al 1990). The experiment lasted 32 d, after which all units were collected and weighed; the stolon length produced was recorded and the final number of assimilators was counted.…”
Section: Methodsmentioning
confidence: 99%
“…The biotechnology of enzymes and enzyme degraded products of carrageenan is still in infancy compared to that of agar, alginate, starch [3] or pectin [4]. Carrageenases which hydrolyse 1,4 linkages in carrageenan to a series of homologous, even numbered oligosaccharides [5] are useful tool for the structural analysis of the cell walls and protoplast isolation from red algae [6,7]. The sulfated carrageeno-oligosaccharides have also drawn considerable interest [8] owing to their diverse biological and physiological activities including anticoagulation [9], anti-inflammation [10], anti-thrombosis [11], antitumor activity [12] and viral inactivation [13], which depend on structural parameters such as carbohydrate structure, molecular mass, degree of sulfate esterification, and the linking position of sulpho groups [14].…”
Section: Introductionmentioning
confidence: 99%